Peningkatan Keterampilan Kolaborasi dan Hasil Belajar Kognitif Siswa dengan Model Pembelajaran Group Investigation pada Materi Bioteknologi - Muhammad Taqiyuddin Hilali; Idayati; Siti Zubaidah (Pro-Life, 2025)
Collaboration skills involve planning and working together by considering multiple perspectives, actively contributing, listening, and supporting others. Collaborative activities in learning produce active learning, facilitating an exchange of knowledge and strengthening student understanding. Based on observations, the cognitive learning outcomes of students in class X-K SMAN 1 Turen regarding virus material were incomplete, with an average score of 63. The collaboration skills score is 47.6%, which falls within the beginner category. Therefore, both aspects need improvement. This study aims to improve students' collaboration skills and cognitive learning outcomes about biotechnology through the application of the Group Investigation model. This research is a Classroom Action Research (CAR) conducted in two implementation cycles. The results indicated that through Group Investigation, students' collaboration skills and cognitive learning outcomes improved. Students' collaboration skills increased from a score of 2.9 (basic) in cycle I to 3.2 (proficient) in cycle II. Cognitive learning outcomes also increased from an N-Gain value of 0.53 (medium) in cycle I to 0.74 (high) in cycle II. Based on these findings, the Group Investigation model is recommended as a practical solution for teachers to improve students' collaboration skills and cognitive learning outcomes.